CHE485: Chemistry Laboratory / College of Engineering - UiTM, College of Engineering (2018)
This course provides a complementary practical experience to the theoretical work studied in the physical, inorganic and organic chemistry courses. The course comprises of open-ended laboratory investigations, which require effective communication, delegation and time-management skills to achieve the experimental aims.